2013
DOI: 10.1891/0886-6708.vv-d-12-00055
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting and Facilitating Factors to End a Violent Relationship: Patterns of Behavior Among Women in Spain

Abstract: The objective of this study are (a) to explore the factors, which facilitate or inhibit women's responses to intimate partner violence (IPV) and their ability to leave a violent relationship; (b) to identify patterns of behavior in abused women based on their perception of the violence and the actions they take to find help or a solution to the problems derived from IPV. Semistructured interviews were carried out. The critical path is defined as the sequence of decisions and actions taken by affected women to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Results indicated that lack of personal resources, such as independent income, and residence and health, was one of the important barriers to leaving a relationship among the participants. In other studies, unemployment and low educational level (Ruiz-Pérez et al, 2013), inability in gaining independent income (Kulwicki, Aswad, Carmona, & Ballout, 2010; Zakar et al, 2012), not knowing English language for immigrant women, lack of knowledge about the provided social and legal services in the community, being an immigrant (Kulwicki et al, 2010), and having poor health (Sabri et al, 2016) were the barriers to leaving a relationship. However, having access to the resources that would decrease dependence on the partner such as job opportunities (Ruiz-Pérez et al, 2013), health (Ruiz-Pérez et al, 2013; Sabina & Tindale, 2008), and independent income or residence (Fanslow & Robinson, 2010) considered as effective factors in leaving a relationship.…”
Section: Discussionmentioning
confidence: 97%
“…Results indicated that lack of personal resources, such as independent income, and residence and health, was one of the important barriers to leaving a relationship among the participants. In other studies, unemployment and low educational level (Ruiz-Pérez et al, 2013), inability in gaining independent income (Kulwicki, Aswad, Carmona, & Ballout, 2010; Zakar et al, 2012), not knowing English language for immigrant women, lack of knowledge about the provided social and legal services in the community, being an immigrant (Kulwicki et al, 2010), and having poor health (Sabri et al, 2016) were the barriers to leaving a relationship. However, having access to the resources that would decrease dependence on the partner such as job opportunities (Ruiz-Pérez et al, 2013), health (Ruiz-Pérez et al, 2013; Sabina & Tindale, 2008), and independent income or residence (Fanslow & Robinson, 2010) considered as effective factors in leaving a relationship.…”
Section: Discussionmentioning
confidence: 97%
“…Domestic violence (DV) is a worldwide phenomenon threatening the lives of millions of people. It violates their basic human rights [ 1 , 2 ]. DV is defined by WHO, as the intentional use of force or power, among members of a particular family or by intimate partners.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide one in three women have experienced at some point of their lives either physical or sexual abuse perpetrated by an intimate partner [ 1 ]. According to population surveys covering high and low-middle income countries (however not including Mozambique), 10% to over 69% of women report having suffered some form of physical or sexual abuse inflicted by an intimate partner at some point in their lives [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heise, Ellsberg, and Gottmoeller, 2002;L. Heise and Garcia-Moreno, 2002;Jewkes, 2002;Krug, Mercy, Dahlberg, and Zwi, 2002;Ruiz-Pérez et al, 2013;White, McMullin, Swartout, Sechrist, and Gollehon, 2008).…”
Section: Introductionmentioning
confidence: 99%